An update on the management of acne vulgaris - Jonette Keri; Michael Shiman (Dove Medical Press, 2009)
Jonette Keri1,2, Michael Shiman11Department of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USA; 2Dermatology Service, Miami VA Hospital, FL, USAAbstract: Acne vulgaris is a common skin disorder that can affect individuals from childhood to adulthood, most often occurring in the teenage years. Acne can have a significant physical, emotional, and social impact on an individual. Many different treatment options are available for the treatment of acne vulgaris. Commonly used topical treatments include benzoyl peroxide, antibiotics, sulfur and sodium sulfacetamide, azelaic acid, and retinoids. Systemic treatment is frequently used and includes the use of systemic antibiotics, oral contraceptives, antiandrogens, and retinoids. Other treatment modalities exist such as the use of superficial chemical peels as well as using laser and light devices for the treatment of acne. With the multitude of treatment options and the rapidly expanding newer technologies available to clinicians, it is important to review and be aware of the current literature and studies regarding the treatment of acne vulgaris.Keywords: acne vulgaris, treatment, benzoyl peroxide, antibiotics, retinoids, lasers